2000
DOI: 10.2105/ajph.90.3.380
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an antismoking media campaign on progression to established smoking: results of a longitudinal youth study

Abstract: A B S T R A C TObjectives. We examined the impact of a statewide antismoking media campaign on progression to established smoking among Massachusetts adolescents.Methods. We conducted a 4-year longitudinal survey of 592 Massachusetts youths, aged 12 to 15 years at baseline in 1993. We examined the effect of baseline exposure to television, radio, and outdoor antismoking advertisements on progression to established smoking (defined as having smoked 100 or more cigarettes), using multiple logistic regression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…This is in line with earlier research, e.g. study conducted by Siegel and Biener (2000). The study showed that media advertisements had effect only among younger adolescents (12-13-year old respondents), whereas it had no effect on older adolescents (aged 14 to 15 years).…”
Section: Limitations and Guidelines For Future Studiessupporting
confidence: 92%
“…This is in line with earlier research, e.g. study conducted by Siegel and Biener (2000). The study showed that media advertisements had effect only among younger adolescents (12-13-year old respondents), whereas it had no effect on older adolescents (aged 14 to 15 years).…”
Section: Limitations and Guidelines For Future Studiessupporting
confidence: 92%
“…It is especially important from a regulatory perspective to understand what types of warnings have an effect that persists over time. While there have been studies that have examined the impact of antismoking media campaigns over time (e.g., Siegel & Biener, 2000), there have been very few studies that have studied the impact of warnings using a longitudinal design (Hammond et al, 2004). In one study that examines the impact of different graphic warning labels, Andrews and colleagues (2014) find that graphic warnings can have a carryover effect on thoughts of quitting smoking for young adult smokers after a one-week delay following exposure to the cigarette package warning.…”
Section: Challenges In Developing Cigarette Warnings and Directions Fmentioning
confidence: 99%
“…In public health, information campaigns have been used to promote safer sexual practices (Alstead et al, 1999), regular monitoring of health (Black et al, 2002; Fender et al, 1999), cessation of smoking (Farrelly et al, 2002; Siegel and Beiner, 2000), and reduction in transmission of infectious diseases (Preston, 1996). Nutrition labels on food products aim to motivate appropriate choice in one’s diet (some relatively recent examples are Harnack and French, 2008; Downs et al, 2009; and Wisdom et.…”
Section: Related Empirical Literaturementioning
confidence: 99%